Comparison of Trauma Scoring Ability to Predict Survival Rate in Countries with Low to Middle-Income - Servasius Ratu Banin; Yuyun Yueniwati; Yulian Wiji Utami (GoAcademica Research & Publishing, 2020)
The use of trauma scoring in the hospital is very important because it has a significant impact both clinically and economically. However, not all trauma scoring that we know today is suitable for use in low to middle-income countries or applied in hospitals with limited resources. The purpose of compiling a systematic review is to identify which trauma scoring is most appropriate for use in low to middle-income countries. This systematic review was built by identifying scientific articles published between 2010-2019. Search for articles was carried out with the keywords